Euglena : biochemistry, cell and molecular biology - Schwartzbach, Steven D.; Shigeoka, Shigeru (Springer, 2017)
"This much-needed book is the first definitive volume on Euglena in twenty-fire years, offering information on its atypical biochemistry, cell and molecular biology, and potential biotechnology applications. This volume gathers together contributions from well-known experts, who in many cases played major roles in elucidating the phenomenon discussed. Presented in three parts, the first section of this comprehensive book describes novel biochemical pathways which in some instances have an atypical subcellular localization. The second section details atypical cellular mechanisms of organelle protein import, organelle nuclear genome interdependence, gene regulation and expression that provides insights into the evolutionary origins of eukaryotic cells. The final section discusses how biotechnologists have capitalized on the novel cellular and biochemical features of Euglena to produce value added products. Euglena: Biochemistry, Cell and Molecular Biology will provide essential reading for cell and molecular biologists with interests in evolution, novel biochemical pathways, organelle biogenesis and algal biotechnology. Readers will come away from this volume with a full understanding of the complexities of the Euglena as well as new realizations regarding the diversity of cellular processes yet to be discovered"--Publisher's description.
Keywords: Euglena -- Composition.; Euglena -- Genetics.; Molecular biology.; Biotechnology.; elektronické knihy; electronic books